SOL-GEL SYNTHESIS AND PROPERTIES OF Co AND Ni-DOPED TiO2 NANOCOM-POSITES FOR OIL AND GAS INDUSTRY WASTEWATER TREATMENT (Scientific journal of the Fergana State University, 2026)
Co and Ni doped TiO2 nanocomposites synthesized by sol-gel method exhibit high photocatalytic activity. In this study, the synthesized nanomaterials were investigated for their potential application in wastewater treatment, particularly environmental treatment. Compared with pure TiO2, Co and Ni doped TiO2 nanocomposites exhibited higher photocatalytic degradation of phenol in aqueous suspension under both UV and visible light. These results indicated that the doping cations could suppress the recombination of electrons and holes. Therefore, the photocatalytic activity of TiO2-based nanomaterials was high.